Strategic Approaches to Activating Academic Entrepreneurship in Modern Mega-Universities: Prospects for Ukraine - Novikova, I.E.; Zhylinska, O.I.; Osetskyi, V.L.; Bediukh, O.R. (Наука та інновації, 2020)
Introduction. Currently, R&D activity is the main in all the top universities in the world because it is focused on the acquisition of new knowledge, while educational is only on the use of acquired knowledge. However, in Ukraine, the trend of academic entrepreneurship development has not yet taken on proper significance. Problem Statement. The implementation of the idea of intensifying the innovation-investment movement in Ukrainian universities involves upgrading the existing innovation-oriented infrastructure and developing an effective plan of action for those universities in which material and technical and intellectual foundation till have a well-preserved. Purpose. formulate strategic approaches to the commercialization of research products in modern mega-universities, which generally involves the intensification of research activities in the context of international academic entrepreneurship education as an imperative for the development of a high-tech, export-oriented and socially responsible model of economy. Materials and Methods. The methods of economic (in particular PEST- and SWOT-analyzes) and logicstructural analysis, methods of comparison, synthesis, forecasting, theoretical generalization, as well as economicstatistical methods of analysis of actual data are used. Results. A result of this initiative is to formulate recommendations and steps to increase the non-budgetary sources of funding for university research and innovation activities in Ukraine, in particular by raising the profitability of intellectual property and the creation of small innovative enterprises. Conclusions. The results obtained will allow us to formulate strategic principles in the development of a new methodological paradigm for the commercialization of the results of intellectual work in universities, taking into account the development trends of the world and the features of national science.